Juegos colaborativos en los niños y niñas de educación inicial - Caisapanta Vizuete, Gessy Marivel (2017)
This project research about collaborative games in initial education children was developed in order to identify the collaborative games elements to determine the contribution of this type of playful strategy in the children development, considering that in children a deficient integration level is evidenced can impair the social skills development at the Initial Education children. The interpretative paradigm with a qualitative and quantitative approach were applied in this research development combined with the bibliographic documentary research which allowed to describe the collaborative game variables and the school integration in the Initial Education frame and field research that made possible to collect information directly from the educational institution studied. A survey, interview, observation sheet are techniques and instruments used of determining the knowledge level and collaborative games use; which will improve the girls and boys integration….